Comparative Analysis of INA-CBGs Tariffs and Unit Cost of Cesarean Section: A Systematic Review in Indonesian Hospitals - Syakurah, Rizma Adlia; Frymaruwah, Edwin; Mufarikhah, Muhimatul; Izzatika, Meiliza (Journal of Public Health Sciences, 2025)
The National Health Insurance (JKN) requires efficient, equitable, and sustainable healthcare services. However, various studies indicate discrepancies between INA-CBGs tariffs and actual hospital service costs. One of the procedures with the highest claim rates is Cesarean Section (CS), which exhibits significant disparities. This study aims to analyze the average unit cost associated with Cesarean Sections (CS) across Indonesia using the Activity-Based Costing (ABC) method. A systematic literature review (SLR) approach was employed, analyzing articles published between 2017–2024. Relevant articles were retrieved through the Google Scholar database. Of the 79 articles initially identified, 37 passed the preliminary screening, and 12 articles met all inclusion criteria. Results indicate that INA-CBGs tariffs for CS procedures only cover 25%–54% of actual costs, varying by service class, hospital location, and operational efficiency. This mismatch contributes to financial deficits in hospitals, potentially compromising service quality, restricting medical equipment procurement, and increasing healthcare professionals’ workloads. Moreover, regional cost variations demonstrate that the current tariff system inadequately considers geographic factors and service complexity. Hospitals in major cities like Bandung report nearly double the unit costs compared to regions such as Yogyakarta or Lampung. Therefore, findings highlight the necessity of reformulating INA-CBGs tariffs to better reflect hospitals' actual conditions. Without updates based on cost-of-service, the financing system risks perpetuating service disparities and reducing the quality of national healthcare. The review findings indicate that the actual cost of Cesarean Section (CS) procedures in Indonesian hospitals is significantly higher than the INA-CBGs tariffs reimbursed by BPJS, with disparities ranging from 46% to 75%.